Хожа Ахмет Яссаўийдиң «Дийўаный ҳикмет» шығармасы ҳәм тәсаўўип талийматы (SCIENCE and SOCIETY, 2026)
The article examines the role of Khoja Ahmed Yasawi’s "Diwani Hikmet" in the spiritual history of Turkic peoples and the core stages of Sufi teaching (shariat, tariqat, ma’rifat, haqiqat). It provides a scientific analysis of the education of the nafs, the concept of the Perfect Man, and the philosophy of love. The influence of the work’s linguistic and poetic features on subsequent Turkic literature is also revealed.